Dancing like a girl: physical competence and emotional vulnerability in professional contemporary dance - Purser, Aimie Christianne Elizabeth. (Human Kinetics, 2017)
The analysis presented here is based on a phenomenological interview study conducted with sixteen professional contemporary dancers, and focuses on the differences between the accounts of male and female dancers with regard to notions of openness in dance and to associated feelings of emotional vulnerability and metaphorical ‘nakedness’ or exposure. In a way that is reminiscent of Young’s (1980) description of ‘throwing like a girl’, such feelings of vulnerability and accompanying self-consciousness were considerably more noticeable in the accounts of the female dancers, tending to emerge when dancers were asked to express something of a personal or private nature through dance in the presence of others. This paper explores potential resonances between feminine throwing experience as conceptualised by Young (1980) and female dancing experience for my interviewees. Significantly, however, it moves beyond a direct parallel with Young’s (1980) work to explore this sense of vulnerability in a context where female dancers did not display the reduced physical competencies typical of ‘throwing like a girl’. The article further suggests that the dualist concepts of transcendence and immanence may not be appropriate for understanding the experience of dance, including its gendered dimensions, and that we should instead look to theorising dancing body-subjectivity in ways that attend to the blurring of the boundaries of such binaries.